Non-invasive detection of cellular bioelectricity based on carbon nanotube devices for high-throughput drug screening - Pui, Tze Sian (2012)
Nanoelectronic biosensors based on readily fabricated networks of single-walled carbon nanotubes (SWNT-net) were used to non-invasively detect cellular bioelectrical signals. This nanotube approach promises applications in both fundamental research and high-throughput drug screening targeting on ion channels.